The multiple values of urban geosites: El Arenal and Viaje a la Naturaleza parks in Mexico City - Marie Noelle Guilbaud; Natalia Isabel Villalba; Eduardo Rodríguez Osnaya; Maria del Pilar Ortega-Larrocea; Silke Cram-Heydrich; Emmanuel Zeno-Lira (Geofísica Internacional, 2024)
Urban geosites are an important resource for science, geoeducation and geotourism that may provide multiple benefits for local communities. The gigantic Mexico City is settled in a paleolake basin sur- rounded by Quaternary volcanic ranges. The SW corner of the city has spread over two of these ranges, Sierra Chichinautzin and the Sierra de las Cruces, leaving few outcrops in the dense urban network that are preserved in public parks. We present here the results of our study of the geological characteristics of two parks managed by local communities. We found surprisingly high geodiversity in these parks and their directly surrounding areas which, along with their accessibility, give them elevated geoeducation and geotourism values. This geodiversity is combined with biodiversity, creating a geo-bio-heritage that is, however, threatened by anthropic activities. We designed geopaths and, as a first approach to the communities, we organized field excursions along them which were highly successful in raising the knowledge and interest of local people on their geo-bio-heritage and also contributed to their aware- ness of anthropic threats that need to be addressed in order to achieve sustainable management for their conservation. Our project hence represents the first step of a strategy to promote the natural heritage to local communities, contribute to its conservation, and reduce the gap between science and society.